The tragedy of the revolution - Cristobal, Adrian E. (Makati City, Philippines Studio 5 Publishing, Inc., 1997)
The Tragedy of the Revolution is a thought provoking essay on the life and death of a great man. ANDRES BONIFACIO (1863-1897), the founder of the Katipunan and FATHER OF THE PHILIPPINE REVOLUTION. Bonifacio lived during the tumultuous period of the late nineteenth century when the Propaganda Movement lded by illustrados Dr. Jose Rizal and Marcelo H. del Pilar was at its peak. Inspired by Rizal's consumin love for country, Bonifacio organidzed the Katipunan, a secret revolutionary society of Filipinos which numbered as many as a few hundred thousand fighting men. Armed with bolos, spears, lances and a few guns, Bonifacio led the Katipunan into a formidable army of soldiers obsessed with one common to liberate their country from vassalage to Spain. After providing a background of Bonifacio's earlier years and examining the probable influences in his life, author Adrian Cristobal makes an analogy of circumstances in Bonifacio's brief but inspiring life with revolutions and revolutionists elsewhere in the world. Becaus Bonifacio perished under circumstances 'that continue to provoke the minds and hearts of historians and writers', Cristobal protrays a scenario and exposes reasons for Bonifacio's untimely and needless execution. The photos in this boke hopefully provide the reader a compelling visual aid in appreciating the exciting, though difficult time of the 1896 Revolution. Katipunan memorabilia, letters, documents and articles have been included to create a truly memorable visual and reading experience for admirers of BONIFACIO and other great Filipino heroes.
Introduction: In Search of the Hero -- Chapter 1: The Birth of a Hero -- Chapter 2: The Making of the Revolutionist -- Chapter 3: Revolution! -- Chapter 4: The Crisis of the Hero -- Chapter 5: Death of a Hero -- Chapter 6: The Tragedy of the Revolution -- Remembering Bonifacio -- Speacial Feature: A Vison of Tomorrow.
In commemoration of the Andres Bonifacio Centennial, May 10, 1997--Title page.
Keywords: Bonifacio, Andres -- 1863-1897.; Katipunan; Philippines -- History -- Insurrection, 1896-1898.; Philippines -- History -- Biography